Answer:
Choice C is correct answer.
Step-by-step explanation:
Given equation is :
2x²-6x+3= 0
ax²+bx+c = 0 is general quadratic equation.
x = (-b±√b²-4ac) / 2a is quadratic formula to solve general quadratic equation.
comparing given equation with general quadratic equation,we get
a = 2 , b = -6 and c = 3
putting above values in quadratic formula: we get
x = (-(-6)±√(-6)²-4(2)(3)) / 2(2)
x = (6±√36-24) / 4
x = (6±√12) / 4
x = (6±2√3) / 4
x = 2(3±√3) / 4
x = 3±√3 / 2
x = 3±1.73 / 2
x = (3+1.73) / 2 or x = (3-1.73) / 2
x = 4.73 / 2 or x = 1.27 / 2
x = 2.37 or x = .63 is solution of 2x²-6x+3 = 0.